Pathways to Hypertension Control: Unfinished Journeys of Low-Income Individuals in Malaysia and the Philippines - Palafox, Benjamin (Archīum Ateneo, 2024)
Background Reducing inequities in hypertension control among those affected in low- and middle-income countries requires person-centred health system responses based on a contextualised understanding of the choices and care pathways taken by those who rely on the services provided, particularly those from poor and marginalised communities. We examine patterns of care seeking and pathways followed by individuals with hypertension from low-income households in the Philippines and Malaysia. This study aims to fill a significant gap in the literature by analysing the stages at which individuals make decisions that may affect the successful control of their blood pressure. Methods This study presents cross-sectional survey data collected as part of the Responsive and Equitable Health Systems-Partnership on Non-Communicable Diseases (RESPOND) project, a longitudinal observational study in low-income communities. The study participants were 1191 randomly selected adults aged 35–70 years with a self-reported history of hypertension or identified as hypertensive through blood pressure screening. Results While most low-income individuals with hypertension in both countries were diagnosed and receiving medication, Malaysians demonstrated higher self-reported medication adherence. Urban areas in the Philippines showed better hypertension management outcomes compared to rural areas. The study also provides insights into the care seeking pathways followed by low-income adults diagnosed with hypertension. Nearly half of these individuals in Malaysia and a third in the Philippines were following pathways where they had never changed or stopped treatment without professional advice, and where they were using and adhering to their prescribed medication. Following such pathways was strongly associated with a greater likelihood blood pressure control in the Philippines, but less so in Malaysia. Conclusions These findings highlight the need for a contextualised understanding of care seeking choices and the importance of person-centred solutions. They offer a typology of hypertension care seeking pathways and a foundation for similar research in other settings.